Failure of tooth eruption and brachydactyly in pseudohypoparathyroidism are not related to plasma parathyroid hormone-related protein levels - Reis, Mariana Tenorio Antunes; Matias, Diogo Toledo; Faria, Maria Estela Justamante de; Martin, Regina Matsunaga (Bone (New York, N.Y.), 2016)
Pseudohypoparathyroidism (PHP) is a genetic disorder characterized by resistance to the peripheral action of PTH due to maternally inherited heterozygous inactivating mutations in the coding sequence of Gsα or intronic regions of GNAS leading to aberrant splice variants (PHP1A), or methylation defects at GNAS (PHP1B). Brachydactyly is a clinical feature associated with both PHP1A and PHP1B, although it is more frequent in PHP1A patients. Loss-of-function mutations in PTHLH, the gene coding for parathyroid hormone related protein (PTHrP) were previously described in some patients with brachydactyly. Primary failure of tooth eruption (PFE) is related to some syndromes involving skeletal development, but it is also known as a nonsyndromic autosomal dominant condition. Previous studies showed that familial nonsyndromic PFE is caused by heterozygous mutations in the gene encoding the G protein-coupled receptor (PTH1R) for PTH and PTHrP. Thus, we hypothesized that PTHrP resistance could result in failure of tooth eruption (FTE) and/or brachydactyly in PHP. Nineteen patients with a molecular diagnosis of PHP underwent dental panoramic radiography (DPR), hand radiography and had their PTHrP levels measured. Patients with alterations at DPR were submitted to clinical dental evaluation. Nine patients had FTE and 7 patients had brachydactyly; 4 patients presented both features and none of them presented high PTHrP levels. Fourteen patients had PTHrP levels within the normal range and only one patient had slightly elevated PTHrP levels. Additionally, three novel GNAS mutations were described. We described the dental abnormalities in a large series of PHP patients that were followed in a single tertiary center. No relationship between plasma PTHrP levels and failure of tooth eruption, dental manifestations of PHP or brachydactyly was found. It is important that doctors pay attention to dental manifestations of the disease in order to refer patients to a proper care with dentists. •Plasma PTHrP levels and failure of tooth eruption or brachydactyly were not related.•Plasma PTHrP levels were not elevated in pseudohypoparathyroidism patients.•Dental abnormalities were described in a large series of pseudohypoparathyroidism patients.•No association was found between failure of tooth eruption and brachydactyly.